2014
DOI: 10.1088/0953-8984/26/38/386001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of A-site disorder in the properties of A2CoMnO6(A = La, Tb)

Abstract: We have studied the structural and physical properties of the La2-xTbxCoMnO6 series. The crystal and magnetic structures of these compounds were determined by x-ray and neutron diffraction techniques. All samples belong to the family of double perovskites with space group P21/n, but the Co/Mn ordering is not perfect, and antisite defects are formed. The concentration of these defects increases for intermediate compositions, indicating that La/Tb disorder influences the Co/Mn arrangement. A ferromagnetic ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 35 publications
9
37
0
Order By: Relevance
“…[10][11] , as previously reported [22,23]. In order to confirm these statements, we explicitly calculate XAS spectra using CTM4XAS code.…”
Section: Methodssupporting
confidence: 66%
See 2 more Smart Citations
“…[10][11] , as previously reported [22,23]. In order to confirm these statements, we explicitly calculate XAS spectra using CTM4XAS code.…”
Section: Methodssupporting
confidence: 66%
“…In particular, the onset of the FM ground state for x=0.5 is at T C =100 K. [11] A preliminary model from powder neutron diffraction patterns, suggests that Mn and Co moments are oriented within ac plane and both ions are meant to have the same magnetic moment, estimated as 2.23(8)μ B for x=0.5, which is below the 3 μ B expected for S=3/2 high spin Mn 4+ and Co 2+ ions but it seems directly related to the number of antisite defects [11]. However, magnetic long range ordering completely disappears for lower and higher Co concentrations (x<0.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…[10], Y 2 CoMnO 6 , with Y 3+ (r = 1.075Å) [18] in the A position, develops an E-type ordering so compounds with smaller atoms in this position should show similar magnetic structure. This is the case for Yb-and Lu-based compounds (r = 1.042 and 1.032Å, respectively) [18], but not for other R 2 CoMnO 6 compounds (R = Ho, Tm, or Er), where the cationic radius of the A atom ranges between [18] 1.072 and 1.052Å and the conventional FM ordering is found [19].…”
Section: Introductionmentioning
confidence: 80%
“…However, there is no clear experimental evidence that Y 2 CoMnO 6 adopts an E-type magnetic ordering, and it contradicts other works that claim a different ordering [12][13][14]. A study in the YMn 1-x Co x O 3 series [12] indicated that YMn 0.5 Co 0.5 O 3 exhibits a partial Mn/Co ordering (around 75%) and a collinear FM ordering similar to the one found in La 2 CoMnO 6 or Tb 2 CoMnO 6 [15,16]. Accordingly, a recent magnetic study of Y 2 CoMnO 6 also reports a collinear FM ordering [13], though the refinements of the neutron patterns suggests a significant number of antisite defects (ASDs), i.e., Mn and Co exchange positions.…”
Section: Introductionmentioning
confidence: 87%